2000
DOI: 10.1002/1097-4628(20001017)78:3<668::aid-app230>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A study of pyridinium-type functional polymers. III. Preparation and characterization of insoluble pyridinium-type polymers

Abstract: The copolymers of 4‐vinylpyridine (4VP), styrene (St) and divinylbenzene (DVB) with varied compositions, P(4VP‐St‐DVB), were synthesized by suspension polymerization using 2,2′‐azobisisobutyronitrile (AIBN) as an initiator. The insoluble (crosslinked) pyridinium‐type polymers in benzyl–pyridinium bromide form, which possess various macromolecular chain compositions, were prepared by the reaction of each P(4VP‐St‐DVB) with benzyl bromide (BzBr), respectively. By using different halohydrocarbon RX in the quatern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…A number of polycations possessing antimicrobial properties were developed for this purpose including ion exchange fibers [8], alkoxysilanes [9], soluble and insoluble pyridinium-type polymers [10,11], polyionenes [12], polymer surfaces derivatized with poly(vinyl-N-pyridinium) [13,14], and immobilized N-alkylated polyethyleneimine [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of polycations possessing antimicrobial properties were developed for this purpose including ion exchange fibers [8], alkoxysilanes [9], soluble and insoluble pyridinium-type polymers [10,11], polyionenes [12], polymer surfaces derivatized with poly(vinyl-N-pyridinium) [13,14], and immobilized N-alkylated polyethyleneimine [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The permanency of the effect depends of course on the stability of the bonding between the biocide and the polymer. Typical examples are polymers substituted by quaternary ammonium salts [12][13][14][15], phosphonium salts [16][17][18] and pyridinium cations [19,20]. As a rule, these cationic biocides interact with the negatively charged membrane of the bacteria, which is accordingly disrupted and disintegrated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous articles have demonstrated the antimicrobial utility of cationic polymers with quaternary ammonium groups (7)(8)(9). In particular, it was reported that quaternary ammonium polyethyleneimine (QPEI) possesses excellent antibacterial activity (10,11).…”
mentioning
confidence: 99%